Workshop to develop gender transformative research methods - Bailey, Arwen; Rietveld, Anne; Begum, Khadija; Osei-Amponsah, Charity; Mosbah, Menna; Jiron, Jean; Tavenner, Katie; Farnworth , Cathy Rozel (2024)
Report from an innovative workshop among CGIAR and partner gender researchers and development practitioners, focusing on developing gender-transformative research methods. The report covers some conceptual background (Forum Theatre, transformative research, gender-transformative research, empowerment and transformative evaluations, and more) plus a list of the methods under development.